Efficacy of an avocado-based Mediterranean diet on serum lipids for secondary prevention after ischemic stroke: a randomized phase 2 controlled pilot trial - Verónica V. Olavarría; Paola R. Campodónico; Valeska Vollrath; Paula von Geldern; Carolina Velásquez; Patricia Pavez; Barbara Valente; Pamela Donoso; Alexandra Ginesta; Gabriel Cavada; Enrico Mazzon; Víctor Navia; et al. (Lipids in Health and Disease)
Abstract Background The impact of a healthy diet on the secondary prevention of ischemic stroke (IS) remains uncertain. Levels of low-density lipoprotein cholesterol (LDL-C) are inversely associated with the risk of IS recurrence. A Mediterranean diet (MeDi), consisting of a preference for fish/poultry, monosaturated fats from olive oil, fruit, vegetables, whole grains, legumes/nuts and limited red meats, animal fats and sweetened beverages, reduces metabolic syndrome, LDL-C levels and stroke risk. Avocados also reduce metabolic syndrome and LDL-C levels but are not part of the traditional MeDi diet. The effects of an avocado-based Mediterranean diet on LDL-C were investigated and compared to those of a low-fat diet in patients with previous IS. Methods The Avocado-Based Mediterranean Diet on Serum Lipids for Secondary Prevention after Ischemic Stroke (ADD-SPISE) was a prospective, randomized, open-label, blinded outcome assessment, phase 2, clinical trial. The participants were adults with an IS in the previous month who were randomly assigned at a 1:1 ratio to a MeDi or a low-fat diet for three months. Outcome assessors of laboratory results and data analysts were masked. The primary outcome was the mean difference in LDL-C between groups at 90 days, adjusted by statin use. Safety, feasibility and acceptability (assessed through a 14-item questionnaire administered to all patients who completed the follow-up) were also evaluated. Results From August 2018 to October 2022, 200 participants were enrolled (97 randomized to the low-fat diet and 103 to the MeDi), with 189 (94.5%) completing the study. There were no significant differences in LDL-C levels between the MeDi group and the low-fat group at 90 days: 66.5 mg/dL (95% confidence interval [CI] 59.6, 73.4) in the MeDi group and 69.9 mg/dL (62.6, 77.2) in the low-fat group at the end of follow-up. The adjusted difference was − 3.4 mg/dL (-13.4, -6.62); P = 0.50. The intervention group showed significant improvements in Mediterranean diet adherence (P < 0.01). Moreover, no significant differences in adverse events were observed between the groups. Conclusion Compared with a low-fat diet, the avocado-based MeDi did not significantly lower LDL-C in IS patients after three months. The intervention was safe, feasible, and well accepted. Larger trials should establish whether longer dietary interventions could yield clinically significant benefits in these patients. The study is registered under ADD-SPISE at www.clinicaltrials.gov . Identifier: NCT03524742.